The Trends Digital Literacy Research in Elsevier: From Research Design to Data Analysis - Gegana Jayapada (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2026)
In recent decades, digital literacy has gained attention as an interesting research field. This study aims to uncover research trends in articles on digital literacy published in Elsevier journals in the last three years (2024–2026). This study uses a content analysis approach. In data collection, 74 articles were identified from Elsevier journal publications that openly highlight digital literacy as a main focus. This investigation uses six indicators: (1) publication trends, (2) research design, (3) research subjects, (4) dominant contexts/topics, (5) data collection instruments, and (6) data analysis techniques. The findings of this study indicate that (1) there has been a significant increase in publications in the last three years (2024-2026), (2) the dominant research design is quantitative, while qualitative, mixed methods, and intervention-based studies are rare, (3) the research subjects include students, professionals, and broader social groups, (4) the dominant context is education, but also includes work, health, and technology adoption, (5) questionnaires and secondary data dominate the research instruments, (6) the data analysis techniques are dominated by SEM/PLS-SEM. Based on the findings of this study, procedurally diverse and context-sensitive longitudinal studies are needed to advance theoretical and practical progress in digital literacy research